The cGAS/STING Pathway: A Novel Target for Cancer Therapy - Gan, Yu; Li, Xiaoying; Han, Shuangze; Liang, Qi; Ma, Xiaoqian; Rong, Pengfei; Wang, Wei; Li, Wei (Frontiers in Immunology, 2022)
As a DNA receptor, cyclic GMP-AMP synthase (cGAS) plays a crucial role in the immune system by recognizing abnormal DNA in the cytoplasm and activating the stimulator of interferon genes (STING) signaling pathway. This signaling cascade reaction leads to an immune response produced by type I interferon and other immune mediators. Recent advances in research have enhanced our current understanding of the potential role of the cGAS/STING pathway in anticancer therapy; however, in some cases, chronic STING activation may promote tumorigenesis. The present review article discusses the biological mechanisms of the cGAS/STING pathway, its dichotomous role in tumors, and the latest advances with respect to STING agonists and antagonists.